Tadarruj dan Tikrar Terhadap Evaluasi Pembelajaran Tartil al-Qur'an Dalam Perspektif Kitab Muqaddimah Ibn Khaldun - PS , Alaika M Bagus Kurnia; Aliah , Nelud Darajaatul (LPPPM STAI Darul Hikmah Bangkalan, 2021)
This study aims to examine more deeply the evaluation of the ideal tartil al-Quran learning in Ibn Khaldun's view. This study uses a qualitative descriptive method using a phenomenological approach. The data collection techniques use observation data, interviews and related references. The data analysis technique also uses four stages, namely data reduction, data classification by structuring several points of analysis related to the conclusion of the analysis. As for the results of this study, (1) only some teachers implemented the tikrar concept. (2) Whereas the tadarruj at Khadijah Middle School was well systematic